Quality Characteristics and Antioxidant Activities of Rice/Adzuki Bean Mixtures Cooked Using Two Different Methods - Koan Sik Woo; Hyun-Joo Kim; Ji Hae Lee; Byong Won Lee; Yu Young Lee; Byoung Kyu Lee; Jee Yeon Ko (Journal of Food Quality)
This study explored the optimal preparation and the antioxidant levels of rice/adzuki bean mixtures. We compared the quality and physicochemical characteristics of cooked mixtures of rice and adzuki beans prepared using normal and high-pressure rice cookers, with and without the addition of alcohol (15%, v/v). The water-binding capacity and swelling power decreased upon addition of adzuki beans, but water solubility increased. The peak, trough, final, and setback viscosities decreased, but the breakdown viscosity increased. The total polyphenol and flavonoid contents increased after addition of adzuki beans. Total polyphenol contents in cooked rice/20% (w/w) Arari and Geomguseul bean mixtures in a normal cooker with addition of alcohol were 3.00 and 3.09 times higher than plain rice. The flavonoid contents were 10.33 and 8.90 times higher than plain rice. The predominant phenolic acids in cooked rice/Arari bean mixtures were p-coumaric acid and trans-3-hydroxycinnamic acid, and in cooked rice/Geomguseul bean mixtures, they were syringic acid and trans-3-hydroxycinnamic acid. Overall, phenolic acid levels were higher in mixtures cooked in plain water. The DPPH- and ABTS-radical-scavenging activities increased upon addition of adzuki beans. DPPH radical-scavenging activities in cooked rice/20% (w/w) Arari and Geomguseul bean mixtures in a normal cooker with addition of alcohol were 9.09 and 9.22 times higher than plain rice. ABTS radical-scavenging activities were 8.74 and 9.01 times higher than plain rice. Moreover, rice/adzuki bean mixtures prepared in a normal cooker, with addition of alcohol, exhibited higher antioxidant levels than other samples. We present the antioxidative properties of rice/adzuki bean mixtures prepared in different ways; these data will aid manufacturers.